Climate change and the growth of the livestock sector in developing countries - Thornton, Philip K.; Gerber, Pierre J. (Springer, 2010)
Livestock production systems will inevitably be affected as a result of changes in climate and climate variability, with impacts on peoples’ livelihoods. At the same time, livestock food chains are major contributors to greenhouse gas emissions. Agriculture and livestock in particular will need to play a greater role than they have hitherto in reducing emissions in the future. Adaptation and mitigation may require significant changes in production technology and farming systems, which could affect productivity. Given what is currently known about the likely impacts on livestock systems, however, the costs of mitigating and adapting to climate change in the aggregate may not represent an enormous constraint to the growth of the global livestock sector, in its bid to meet increasing demand for livestock products. Different livestock systems have different capacities to adapt or to take on board the policy and regulatory changes that may be required in the future. Vulnerability of households dependent on livestock, particularly in the drier areas of developing countries, is likely to increase substantially, with concomitant impacts on poverty and inequity. The capacity of these systems to adapt and to yield up their carbon sequestration potential deserves considerable further study. Comprehensive frameworks need to be developed to assess impacts and trade-offs, in order to identify and target adaptation and mitigation options that are appropriate for specific contexts, and that can contribute to environmental sustainability as well as to poverty alleviation and economic development.